A multidimensional assessment of the burden of psoriasis: results from a multinational dermatologist and patient survey3. (24th April 2018) - Griffiths, C.E.M.; Jo, S.‐J.; Naldi, L.; Romiti, R.; Guevara‐Sangines, E.; Howe, T.; Pietri, G.; Gilloteau, I.; Richardson, C.; Tian, H.; Augustin, M.
Summary: Background: Psoriasis is a chronic, immune‐mediated disease, characterized by symptoms that include itching and skin pain and is often associated with comorbidities. Patients have a substantial detriment to quality of life (QoL) and work productivity with associated cost burden. Objectives: To investigate the incremental burden of comorbidities, itch and affected body areas among systemic eligible patients with psoriasis, using a multinational survey of dermatologists and their patients with psoriasis. Methods: Multinational data from the Growth from Knowledge (GfK) Disease Atlas Global Real‐World Evidence program were used. Eligible patients were identified as those who were currently having or had ever had moderate‐to‐severe psoriasis, and must have been receiving prescription treatments at the time of the survey. Multivariable regression analyses were conducted to assess the incremental burden among psoriasis patients with physical and psychological comorbidities, itch and affected visible and sensitive body areas vs. psoriasis patients without these conditions, respectively. Results: The study enrolled 3821 patients with psoriasis, from nine countries, with an average Psoriasis Area and Severity Index score of 6·4. The presence of comorbidities was associated with a significant increase in the likelihood of skin pain, lower QoL, greater work impairment and increased usage of medical resources (except in psoriasis patients with obesity and type 2 diabetes). Psoriasis patients suffering from itch and those with visible and sensitive affected body areas also had impaired QoL vs. those without these conditions. Conclusions: Psoriasis patients with physical and psychological comorbidities, itch and affected visible and sensitive body areas had lower QoL and greater work impairment compared to those without these conditions. Abstract : What's already known about this topic? Psoriasis is a chronic, immune‐mediated inflammatory disease that causes great physical, emotional and social burden. Psoriasis is associated with a higher risk of physical and psychological comorbidities; along with bothersome symptoms of itch and presence of the disease on visible and sensitive body areas. Presence of associated comorbidities, itch and lesions on visible and sensitive body areas in patients with psoriasis are closely related to decreased psychosocial well‐being and have an impact on quality of life. What does this study add? Results suggest that the clinical, humanistic and economic burden of psoriasis is complex and multidimensional, and not just determined by the severity of disease. Multiple aspects of psoriasis such as associated physical and psychological comorbidities, itch and type of body areas affected by psoriasis contribute to increase this burden further. Linked Comment: Gisondi. Br J Dermatol 2018;179 :13–14 . Plain language summary available online Respond to this article